PERANCANGAN SISTEM PEMESANAN PERCETAKAN PADA TOKO BORNEO - Halimatussa’diah Halimatussa’diah; Andri Nursya’ban (Sekolah Tinggi Pariwisata Mataram, 2022)
Borneo Store is a company or agency that is engaged in printing and selling stationery. At this time the printing system carried out at the Borneo store is still running with a series of processes where customers come directly to the physical store and may queue with other customers to print documents, which will slow down other activities of the customer. In this problem, an idea arises to create a website system that can make it easier for customers to order printing online, where customers only need to upload documents to be printed and wait for confirmation by the service provider for orders that have been processed Research method Research and Development (R&D), Research and Development (R&D) is a research method where the author designs and builds an information system or program which is then applied to Toko Borneo, covering the initial process of designing to implementing the program. This system uses the PHP programming language with the database management system used is Mysql. The results of this study are a website-based printing order information system that makes it easier for customers to print without having to carry documents and queue with other customers at the printing location.